Rice husk gasifier in UiTM Penang as energy : a design review / Mohd Mahadzir Mohammud (Dr.) and Muhammad Dzulkifli Zikri - Mohammud, Mohd Mahadzir (Dr.); Zikri, Muhammad Dzulkifli (Universiti Teknologi MARA, Perak, 2017)
To reduce dependency on fossil fuel, reduce pollution and move into green technology, the rice husk gasification has been developed as the process that converts organic rice husk into a producer of gas. However, drawbacks such as grate blocking, bridging and suitability of feedstock are found in the gasifiers. Design of the gasifiersis an important objective and improvements on the design have been done to enhance the performance of the gasifiers. This paper aims to review gasifiers focused on design improvements. Many works from previous researchers have been studied. The result shows the new design of the gasifiers is an important parameter in gasification